Analisis Perencanaan Strategi Sistem Informasi Dan Teknologi Informasi Pada PT. OCT Menggunakan Metode Ward And Peppard - Sudrajat Sudrajat; Santi Puspa Oktaviane; Novi Rukhviyanti (International Forum of Researchers and Lecturers, 2024)
Introduction: The rapid development of Information Systems (IS) and Information Technology (IT) has influenced all business sectors. One of the business sectors that is influenced by the application of IS/IT is the manufacturing industry as carried out by the company PT.OCT. This article aims to analyze information systems strategic planning Method: using the Ward & Peppard method, there is also PESTEL, Value Chain, SWOT, CSF analysis, application mapping with McFarlan Grid, and IS analysis, this method is useful for designing appropriate information system architecture, and integrating information technology into overall business strategy . Analysis: analysis of the internal business environment using Value Chain analysis, then Porter's Five Forces analysis was chosen as the analysis of the external business environment. Conclusion: The results of the analysis show that the application of the Ward and Peppard method provides the final result which is an IS/IT strategic document that is effective in helping business processes at PT. OCT is engaged in manufacturing.